Globalization of Curriculum at Private Tsanawiyah Madrasah Muallimin Univa Medan - Muhammad yunus; Yurmaini Yurmaini; Hotni Sari Harahap (Edumaspul: Jurnal Pendidikan, 2023)
This study aims to determine the concept of glocalization of the curriculum at the Muallimin UNIVA Medan Private Tsanawiyah Madrasah and the strategies used by the Muallimin UNIVA Medan Private Tsanawiyah Madrasah in implementing the concept of glocalization. This type of research is qualitative research with a phenomenological approach (according to existing phenomena). The data sources used are primary and secondary data, in which the primary data is obtained from 5 main informants. Data collection methods used are interviews, observation and documentation. The data analysis technique in this study used 3 stages, namely data reduction, data presentation and conclusions. While the data guarantee tool used is triangulation. The results of the study concluded that the concept of glocalized curriculum is combining 3 curricula in learning, namely the K13 curriculum, the Ministry of Religion curriculum and the Ke Al-Washliyahan curriculum. The strategy used in implementing the concept of glocalization of the curriculum is when the learning process (teaching-learning) takes place, selection of prospective teachers, formation of student character values ​​​​and several competitions are held.